KAJIAN HADITS TENTANG PENTINGNYA SALAM SEBAGAI SARANA PENDIDIKAN ANAK AGAR BERBAKTI KEPADA ORANG TUA - Burhanuddin Ridlwan; Laily Masruroh; Syamsuddin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2019)
The hadith about the importance of greetings as a means of education and habituation of children to be devoted to parents, which is contained in the book of Imam al-Bukhari